Generation of a bovine BAC pool for chromosome region BTA7q14-22 correlated to the trait trypanotolerance - Goldammer, T.; Brunner, R.M.; Kang'a, S.; Hanotte, Olivier H.; Schwerin, M. (1999)
Trypanosomiasis is one of the most important diseases in African cattle. About 3 million cattle die every year by this disease. However, about 5 percent of the total African cattle have a natural resistance against trypanosomiasis. In a preliminary study markers linked to trypanotolerance have been identified on different chromosomes. The use of these information in breeding programs needs a close linkage of DNA markers to the trait. Therefore, a goal of the research on domestic cattle in Africa is the generation of a high resolution marker map for QTL regions significantly affecting trypanotolerance. An experimental approach for the direct analysis of chromosome regions correlated to economically important traits is microdissection. The chromosome fragment BTA7q14 - q22 which corresponds to the QTL linked to parasitaemia was isolated several times and used for the generation of chromosomal libraries. Primers designed from chromosome fragment specific sequences were used for the isolation of bovine specific BACs (bacterial artificial chromosomes) which now serve as starting material for the identification of informative markers within the QTL region.